A LIST OF THE BUTTERFLIES OF UJUNG KULON NATIONAL PARK, JAVA, INDONESIA - Djunijanti Peggie (Treubia, 2012)
The occurrence of butterfly species at Ujung Kulon National Park is presented based on collection and observation data obtained in 2005, 2006 and 2010 and previous reports. As many as 101 butterfly species were recorded during the recent surveys. The data are compared with previous findings. To date, there are 177 species reported from Ujung Kulon.